Asymptomatic severe aortic stenosis, conservative treatment or early valve replacement? a systematic review and meta-analysis. (11th May 2022) - K Awad, A; Elseidy, S; Elgenidy, A; Elbadawy, M A; Sayed, A; Mohamad, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Asymptomatic aortic stenosis' management is not only a daily practice challenge but also an area of clinical research controversy. As evidence on conservative versus early aortic valve replacement (AVR) is debatable, we conducted a systematic review and meta-analysis to compare the efficacy of conservative management versus AVR in asymptomatic aortic stenosis (AS). Methods: Electronic databases were systematically searched to identify any observational or interventional studies that compared the effects of conservative management versus AVR on all causes, cardiovascular, non-cardiovascular mortality. Pooled risk ratios (RR) and their 95% confidence intervals (CI) were calculated using random-effects models. Results: A total of 6216 patients were included from 12 studies (observational=9, and randomized clinical trial=3) with a mean follow-up duration of 50 months. When compared to early AVR, conservative management has statistically significant higher risk of all causes mortality (RR: 0.36, 95%CI [0.31 to 0.42], p<0.00001, figure 1), cardiovascular mortality (RR: 0.32, 95%CI [0.24 to 0.41], p<0.00001, figure 2), and non-cardiovascular mortality (RR: 0.42, 95%CI [0.24 to 0.56], p=0.0005). Regarding other complications, conservative treatment showed significant higher risk of sudden cardiac death (RR: 0.46, 95%CI [0.15 to 0.90], p=0.005), yet with no difference over AVR in stroke and myocardial infarction (RR: 0.79, 95% CI [0.17 to 3.64], p=0.61) and (RR: 0.67, 95% CI [0.39 to 1.16], p=0.15), respectively. A subgroup sensitivity analysis based on surgical AVR vs. transcatheter AVR and severe vs. very severe AS reflected the findings of the overall results. Conclusions: Patients with asymptomatic aortic valve stenosis, managed with early AVR, have a lower risk of all-cause, cardiovascular, and non-cardiovascular mortality when compared to conservative management.